Perancangan Leaf Vacuum 2in1 untuk Mengurangi Risiko Musculoskeletal Disorders (MSDs) menggunakan Metode Ergonomic Function Deployment (EFD) - Nabila, Azzahra Yandra; Mufidah, Ilma; Martini, Sri (Innovative: Journal Of Social Science Research, 2024)
Telkom University is one of the universities that offers a beautiful green atmosphere from trees. However, the impact given is a lot of leaf waste that fall in the campus area. Currently, the janitors still use manual methods to clean leaf waste, so that makes the work posture not ergonomic and causes a risk of Musculoskeletal Disorders (MSDs). Based on the problems, a research was conducted to develop a semi-automated tool using Ergonomic Function Deployment (EFD) method to reduce the risk of Musculoskeletal Disorders (MSDs). This tool is called Leaf Vacuum 2in1 which has a vacuum feature as well as a shredder for leaf waste. In the design process, Leaf Vacuum 2in1 considers the ergonomics principles (ENASE) and uses anthropometry data. Based on REBA analysis, it found that the score of the original work posture of 8 changed to 3. This score indicating a low risk when the janitor uses Leaf Vacuum 2in1. Therefore, Leaf Vacuum 2in1 has the potential to reduce the risk of Musculoskeletal Disorders (MSDs)